Maternal diet associated with infants’ intestinal microbiota mediated by predominant long-chain fatty acid in breast milk - Xi, Menglu; Na, Xiaona; Ma, Xia; Lan, Hanglian; Sun, Ting; Liu, Wei-Hsien; Hung, Weilian; Zhao, Ai (Frontiers in Microbiology, 2023)
Long-chain fatty acids in breast milk are affected by the mother's diet and play an important role in the growth, development, and immune construction of infants. This study aims to explore the correlation between maternal diet, breast milk fatty acids (FAs), and the infant intestinal flora. We enrolled 56 paired mothers and their infants; both breastmilk samples and infants’ fecal samples were collected to determine the long-chain FA content of breast milk by ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS), and metagenomic technology was applied to determine the microbial composition of infant feces. The maternal diet was also investigated using a 24-hour dietary recall. The results indicated that the fat contribution rates of edible oils in the maternal diet are significantly positively correlated with the contents of certain long-chain fatty acids (C16:0, C18:1, C16:1, and C22:4) in breast milk, which mainly regulate the abundance of Lacticaseibacillus rhamnosus, Lacticaseibacillus fermentum, and Lacticaseibacillus paracasei in the infant gut. Through KEGG pathway analysis, our data revealed that the long-chain FAs in different groups of breast milk were significantly correlated with the pathways of biotin metabolism, glycerolipid metabolism, and starch and sucrose metabolism. In conclusion, the results of this study suggest a pathway in which the diets of lactating mothers may affect the composition of the infant intestinal microbiota by influencing breast milk FAs and then further regulating infant health.